Peran Kepuasan Peserta Sebagai Variabel Mediasi Dalam Pengaruh Kualitas Pelayanan dan Komunikasi Field staff Terhadap Efektivitas Program Fasilitasi Pendampingan Usaha Akses Reforma Agraria Tahun 2025 - Syekh Ja’far Shodiq; Yuni Kasmawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the influence of service quality and communication of Field staff on the effectiveness of the Business Assistance Facilitation Program within Agrarian Reform, with participant satisfaction as a mediating variable. The study is motivated by the need to ensure that agrarian reform programs not only focus on asset legalization but also support sustainable economic empowerment for beneficiary communities. A quantitative approach was employed using a survey of program participants who directly interacted with Field staff as technical implementers in the field. The findings indicate that service quality and communication do not directly determine program effectiveness but operate through participant satisfaction as a response to the assistance process. This study emphasizes that business assistance should not be interpreted as a reflection of limited community capacity, but rather as a facilitative and coordinative mechanism to strengthen existing economic potential, indicating that program effectiveness depends on institutional role alignment, participatory service approaches, and respect for community autonomy.